Root and Shoot Traits of Spring Wheat Cultivars with Wild-Type and Semi-Dwarf Rht Alleles at Early and Late Growth Stages - Hayati Akman; Philip Bruckner (Turkish Journal of Agriculture: Food Science and Technology)
Roots play an important role in improving crop yield by affecting the amount of water uptake and nutrient acquisition. The objective of this study was to characterize variability in root and above-ground characteristics among three diverse semi-dwarf spring wheat cultivars, ‘Vida’, ‘Oneal’ and ‘Duclair’ and a wild-type cultivar, ‘Scholar’ at early and late growth stages in a greenhouse. Plants were grown in 45-cm long tree pots in a greenhouse under optimal growth conditions. As soil-less media, a mixture of peat (70%) and perlite (30%) was used. Plants were harvested at tillering (GS25-26) with 5-6 tillers, booting (GS43-45), and maturity (GS92). Root and shoot traits indicated significant variability among wild-type and semi-dwarf spring wheat cultivars at those growth stages. The study results showed that root mass per plant at tillering, booting, and maturity ranged from 0.10 to 0.14 g, 0.47 to 0.9 g, and 0.55 to 0.85 g, respectively, while shoot mass per plant varied from 1.7 to 2.5 g, 6.5 to 10.7 g, and 21.2 to 24.5 g, respectively. From booting to maturity, root mass was relatively constant, however, shoot mass increased considerably. Moreover, the average root mass of semi-dwarf spring wheat cultivars was 37% lower at booting and 30% lower at maturity compared to the wild-type cultivar, even though there was no significant variation among the cultivars at the early growth stage. Based on the results of the variability identified in this research, wild-type cultivar, Scholar can be evaluated for the improvement of genotypes with superior root system in breeding programs.